2013
DOI: 10.7852/ijie.2013.27.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Awareness and Concept of Insects in Korea

Abstract: To investigate the degree of individuals' concept and awareness of insects, a survey study was conducted with students and adults living in Korea. The misconception rate for insects was about 50% for both students and adults, but it was lower for students and people who had experienced insect-related events than for adults and those who had not. The highest misconception rate was obtained in answer to a question about the basic structure of an insect. Most people had a high awareness of insects. Significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The questions were simple and clear, and the questionnaire's reliability and stability had been previously demonstrated (Bae et al . , ). One to two‐hour insect‐mediated mental healthcare program sections were run in the afternoon once weekly for eight weeks (Table ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The questions were simple and clear, and the questionnaire's reliability and stability had been previously demonstrated (Bae et al . , ). One to two‐hour insect‐mediated mental healthcare program sections were run in the afternoon once weekly for eight weeks (Table ).…”
Section: Methodsmentioning
confidence: 97%
“…The questionnaires included items that measured depression, self-worth, selfconcept, satisfaction with school life, knowledge of insects, affinity for insects and interest in insects. The questions were simple and clear, and the questionnaire's reliability and stability had been previously demonstrated (Bae et al 2013(Bae et al , 2014. One to two-hour insect-mediated mental healthcare program sections were run in the afternoon once weekly for eight weeks (Table 1).…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaires included items that measured planning, subjective quality of life, self-reported depression, self-worth. The questions were simple and clear, and the questionnaire's reliability and stability had been previously demonstrated (Bae et al, 2014;Bae et al, 2013). One or twohours insect-mediated mental healthcare program sections were run in the morning once weekly for 10 wk ( therapy, art therapy, play therapy, drama therapy, horticultural therapy, dance therapy, and animal-assisted therapy (Marcus 2013;Maratos et al, 2011;RenXia 2013;Chinekesh et al, 2014;Hussain 2010).…”
Section: Designmentioning
confidence: 99%
“…Previous studies showed that insects are felt mostly positive in people through surveys of peoples' preferences for insects (Bae et al, 2014;Bae et al, 2013). The rearing and observation of insects and insect-related events may provide positive feelings and even affection in adolescents.…”
Section: Designmentioning
confidence: 99%